Basic Overview of Mobile Cloud Computing (International Journal of Engineering and Computer Science, 2014)
Mobile Cloud Computing (MCC) is a combination of Cloud computing and mobile networks. It is a technique or model in which mobile applications are built, powered and hosted using cloud computing technology.   The capabilities of mobile devices have been improving quickly than computers. Many researchers focus on the area of mobile computing and cloud computing. The mobile computing means to access shared data or infrastructure through portable devices like PDA, smart phone, tablet and so on. Independently from physical location and cloud computing means a virtual computing, distributed computing or resources sharing. Mobile uses the cloud for both application development as well as hosting. The most of application in mobile is cloud based application i.e. IE, social networking apps like facebook apps, that accessible through cloud (internet). It provides the user to interface the data and services on the cloud platform .The mobile computing needed to be limited energy than regular cloud computing.